1970
DOI: 10.1111/j.1445-2197.1970.tb04057.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Preoperative Stay in Hospital and Postoperative Infection

Abstract: This investigation demonstrates that postoperative infection increases with the period of time over which the patient has been in hospital before operation, presumably exposed to skin colonization by “hospital” bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…55 of our patients (83.3%) were over 28 years of age. MCEWIN [20] reported that postoperative infection increases with the period of time over which the patient has been in hospital before operation, presumably exposed to skin colonization by "hospital" bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…55 of our patients (83.3%) were over 28 years of age. MCEWIN [20] reported that postoperative infection increases with the period of time over which the patient has been in hospital before operation, presumably exposed to skin colonization by "hospital" bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Although this does not exclude sources of the same organism in food or wards, it makes theatre infection a serious possibility. Factors increasing liability to post-operative infection have been reviewed (McEwin, 1970). Pseudomonas infection was related to poor condition of the patient.…”
Section: Discussionmentioning
confidence: 99%